Biomass-derived porous heteroatom-doped carbon spheres as a high-performance catalyst for the oxygen reduction reaction. (24th August 2016) - Wang, Guanghua; Peng, Hongliang; Qiao, Xiaochang; Du, Li; Li, Xiuhua; Shu, Ting; Liao, Shijun
Abstract: A high-performance, spherical, heteroatom-doped carbon catalyst for the oxygen reduction reaction (ORR), with a porous structure and a high surface area, has been prepared through a hydrothermal treatment process and subsequent carbonization procedures using brewer's yeast powder, ferric chloride, and ammonium hydroxide as precursors. We found that the addition of iron had a significant effect on the catalyst's spherical morphology and ORR activity. Electrochemical measurements demonstrated that the catalyst has excellent ORR performance, with a half-wave potential 28 mV more positive (0.861 V vs. RHE) than that of commercial 20 wt.% Pt/C (0.833 V vs. RHE) in an alkaline medium. The catalyst also displays remarkable methanol tolerance and durability. The abundance of active N and P species and the porous structure may be responsible for this catalyst's high ORR performance. The present work provides a facile way of using economical, environmentally friendly, and renewable biomass to develop a high-activity cathode electrocatalyst for fuel cell applications. Graphical abstract: A heteroatoms-doped hollow biocarbon spheres with high surface area and hierarchical porous structure were successfully prepared by hydrothermal treating and followed pyrolyzing the mixture of brewer's yeast powder, ferric chloride and ammonium hydroxide. The catalyst displays excellent ORR catalytic activity in alkaline medium, with a 28 mV positive shift (0.861 vs. 0.833 V) in half-wave potential compared to that of commercial 20 wt.% Pt/C (JM) . Highlights: A heteroatoms-doped biocarbon spheres are prepared with brewer's yeast powder as precursor. The addition of Fe plays a crucial role for the formation of spherical morphology. The spheres are abounded with heteroatoms (N, O, P, Fe) and hierarchical porosity. The material shows superior ORR activity to 20 wt.% Pt/C (JM) catalyst in KOH solution.